Know your woods: new wood identification tools for professionals of the sector - Ruffinatto F; Castro G; Cremonini C; Crivellaro A; Urso T; Zanuttini R (Forest@, 2020)
Illegal logging and related illegal timber trade are currently recognized as one of the world’s most pressing environmental problems. In several timber-exporting countries most of the trees are illegally cut, resulting in significant losses of incomes and irreversible damage to forests. In the last years several laws and regulations have been introduced to tackle global illegal trade of wood, such as the 2008 amendment to the US Lacey act, or the European Timber Regulation (EUTR). Professionals of the timber sector are therefore more and more called to a better knowledge of the material they are dealing with, and the identification of the wood species is one of the crucial steps necessary to verify timber legality. In this paper we introduce some recently developed tools aimed at facilitating non-experts to effectively identify wood through macroscopic analysis and possibly find substitutes for woods of uncertain legality.